Ductal aneurysm masquerading as nonresolving pneumonia: A challenging differential! - Chodhary Maitri; Tomar Munesh; Radhakrishnan Sitaraman (Wolters Kluwer Medknow Publications, 2010)
We report here, the case of a six-and-a-half-month-old boy investigated for persistent respiratory distress and homogeneous opacity in the left upper lobe. Echocardiography revealed a giant ductal aneurysm compressing the left pulmonary artery and upper lobe division of the left bronchus. Computerized tomography angiogram delineated the exact anatomy and prompt surgical resection provided a successful cure to this lesser known entity.